Didactic model of treatment to the discalculia in escolars of the Primary Education (Original) (Revista científica Olimpia, 2019)
This work has as objetive:offering the foundations for the elaboracion of a didactic model of treatment to the discalculia in escolars of the primary education, in which it is defined your component and the dialectic relations that it is established among them ,it is made concrete in a new resultan an inclusive guality. The obtained results make evident the fulfillment of the objective of the investigation.
Keywords: escolars, discalculia, didactic model, treatment, primary education